THE EFFECT OF ABRUPT CHANGES IN SALINITY ON THE SFG OF THE MUSSELS - Henna Rya A. Sunoko (JOURNAL OF COASTAL DEVELOPMENT, 1997)
Mytilus edulis of over one year old were exposed to three different proportion of fresh and salt water for seven days. The objective of the study is to evaluate Scope For Growth (SFG), using the physiological responses of mussels as a potential monitor of the impact of environmental stresses. The feeding rates, respiration rates, food absorption efficiencies, and SFG of the mussels were measured following the seven day exposure period. Clearance rates relatively showed a small decrease with exposure to decreasing salinities, but it was not statistically significant. Absorption efficiencies of the mussels in the three groups were generally not different. Respiration rates among the three groups were not effected by, but changed consistently with increasing proportions of fresh water. The SFG among the three groups did not differ significantly by Anova, but the P value (0.069) is very close to the level considered significant (0.05). this study suggests that the decreasing salinity “stressed” the mussels.The selected raw materials, generally contains 10 essential amino acids (Arginine, lysine, histidine, phenylalanine, leucine, isoleucine, methionine, valine, threonine, and trypthophane) and a long chain of EFA (n-3 HUFA) and (n-6 HUFA) which are required by mud crab for their growth. The selected local raw materials are therefore nutritionally suitable for mud crab feed development in Central Java.